1966
DOI: 10.1111/j.1744-7348.1966.tb06876.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of barley yellow dwarf virus on the growth and yield of single plants and simulated swards of perennial rye‐grass

Abstract: Irish perennial rye-grass plants infected with barley yellow dwarf virus (BYDV) showed inconspicuous leaf symptoms but were more stunted and yielded less total herbage, but more early spring herbage, than healthy plants. During a period of 2 years, infection did not decrease plant survival; infected plants produced more tillers and gave a higher ratio of vegetative to fertile tillers than healthy plants. BYDV caused a greater loss of yield in simulated rye-grass swards cut twice a year than in those cut four t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
3

Year Published

1977
1977
2009
2009

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 10 publications
1
25
3
Order By: Relevance
“…Possibly a combination of the higher nitrogen status and less frequent defoliation of the British swards accounts for the different effects of BYDV on herbage yields in the two trials. Catherall (1966) also reported that BYDVinfected ryegrasses not only began growth 2-3 weeks earlier and outyielded healthy plants in spring but they also tillered more than did healthy plants. These observations were made on individually grown plants and so they cannot be compared with our data obtained from simulated swards.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Possibly a combination of the higher nitrogen status and less frequent defoliation of the British swards accounts for the different effects of BYDV on herbage yields in the two trials. Catherall (1966) also reported that BYDVinfected ryegrasses not only began growth 2-3 weeks earlier and outyielded healthy plants in spring but they also tillered more than did healthy plants. These observations were made on individually grown plants and so they cannot be compared with our data obtained from simulated swards.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of BYDV on ryegrass in simulated swards was first studied by Catherall (1966) at the Welsh Plant Breeding Station, Aberystwyth. It is therefore germane to compare our data with that from the British trial, bearing in mind the differences in c1imate, strains of BYDV, and plant varieties used.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Virus infections can be ubiquitous in wild plant populations (MacClement and Richards 1956, Yahara and Oyama 1993, Malmstrom et al 2005, can cause significant reductions in vegetative and reproductive performance (Friess and Maillet 1996, Funayama et al 1997, Power 2002, and can alter intra-and interspecific 3 E-mail: kdl24@cornell.edu competitive interactions in plant communities (Catherall 1966, Catherall and Griffiths 1966, Friess and Maillet 1997, Power and Mitchell 2004. Few studies, however, have comprehensively measured fitness impacts of viruses or directly assessed the impact of virus-resistant transgenes on plant fitness (but see Fuchs et al 2004b).…”
Section: Introductionmentioning
confidence: 99%
“…BYDV infection in ryegrasses reduces dry matter yield by as much as 24% (Catherall 1966;Wilkins and Catherall 1977). RMV infection in ryegrasses results in dry matter reductions of 5 -50% (A 'Brook and Heard 1975;Jones et al 1977;Eagling et al 1992).…”
Section: Transgenie Approaches To Enhance Resistance To Viral Diseasesmentioning
confidence: 96%